SIKAP MASYARAKAT DAN KONSERVASI KASUS STIMULUS PAKIS SAYUR DI DESA GUNUNG BUNDER II, KECAMATAN PAMIJAHAN, BOGOR - Zakiyyah Zakiyyah; Ervizal A.M. Zuhud; Sumardjo Sumardjo (Graduate School Bogor Agricultural University (SPs IPB), 2016)
Vegetable ferns (Diplazium esculentum (Retz) Sw) which grows in the forest directly utilized by community and often does not take into account the survival. Utilization of vegetables ferns should be in line with its preservation is to do conservation actions that are based on sustainable development in line with the Regulation of Law No. 5 In 1990 , concerning the conservation of natural resources. To support the law, community’s attitudes must be constituted in accordance with the concept of